The nonlinear transmission problem with memory - L. H. Fatori; D. Andrade (Boletim da Sociedade Paranaense de Matemática, 2004)
In this work we study a nonlinear transmission problem for the waveequation with boundary dissipation of memory type. The material is constituted by two different elastic components. We have a transmission problem with damping boundary condition of memory type. We prove the global existence and uniformly decay of the solution to zero as time goes to infinity.